Search for CP violation using T-odd correlations in D0 → K+K−π+π− decays - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We search for CP violation in a sample of 4.7×104 Cabibbo suppressed D0→K+K−π+π− decays. We use 470 fb−1 of data recorded by the BABAR detector at the PEP-II asymmetric-energy e+e− storage rings running at center-of-mass energies near 10.6 GeV. CP violation is searched for in the difference between the T-odd asymmetries, obtained using triple product correlations, measured for D0 and ¯¯¯D0 decays. The measured CP violation parameter is AT=(1.0±5.1stat±4.4syst)×10−3.